Pengaruh Digital Literacy, Islami Financial Literacy dan Islamic Branding Terhadap Minat Menabung Bank Syariah Pada Generasi Z di DKI Jakarta - Ananda Norma Elvira Ramadan; Ummu Salma Al Azizah; Nugroho, Arif Widodo; Irsyad Ali Amin (Pusat Riset dan Inovasi Nasional, 2026)
This research seeks to examine the impact of digital literacy, Islamic financial literacy, and Islamic branding on Generation Z’s interest in saving with Islamic banks in DKI Jakarta. Unlike most prior studies, this work highlights the combined role of digital literacy, Islamic financial literacy, and Islamic branding, specifically focusing on Generation Z in DKI Jakarta, which has not been widely explored. A quantitative research design was applied, with data gathered through a questionnaire distributed to 400 respondents using purposive sampling. The analysis employed PLS-SEM with the SmartPLS 4 software. The study revealed that digital literacy positively influences saving interest with a coefficient of 0.074, Islamic branding has a strong positive influence with a coefficient of 0.915, while Islamic financial literacy shows no significant effect with a coefficient of -0.002. The model obtained an R-square value of 0.894. This research is restricted to a particular scope or sector, thus the findings cannot be generalized to all contexts. Nevertheless, the results provide useful insights for practitioners, policymakers, and academics in formulating relevant actions or decisions.